Eucalyptus major (Maiden) Blakely and Melaleuca alternifolia (Maiden and Betche) Cheel Leaf Solutions Inhibit the Growth of Antibiotic-Sensitive and β-Lactam Resistant Bacterial Pathogens - Dumont, Eléonore; Cordon, Marie-Elisabeth; Baghtchedjian, Linn; Zai, Muhammad Jawad; Cock, Ian Edwin (Pharmacognosy Communications)
Background: The increased prevalence of antibiotic-resistant bacterial pathogens has substantially decreased the efficacy of some antibiotics and has rendered others completely ineffective. Widespread bacterial resistance to β-lactam antibiotics (including resistance to the second-generation drug methicillin) is particularly concerning and new antibiotic therapies are urgently needed. Materials and Methods: The antibacterial activity of commercially sourced water-soluble Eucalyptus major and Melaleuca alternifolia leaf solutions was screened against β-lactam resistant and sensitive bacterial strains of Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus using disc diffusion assays. The activity was quantified by broth microdilution minimum inhibitory concentration (MIC) assays. Toxicity was evaluated by testing Artemia nauplii mortality assays. Results: Methanolic and aqueous extracts prepared from Eucalyptus major and Melaleuca alternifolia leaves displayed noteworthy growth inhibitory activity against all of the bacteria tested, including against methicillin resistant Staphylococcus aureus MRSA and extended spectrum β-lactamase (ESBL) strains of E. coli and K. pneumoniae. The methanolic E. major leaf extract had particularly good antibacterial activity (MICs=39-625 μg/ mL) against all bacterial strains. Notably, this extract had similar potency against an ESBL strain of E. coli as against the corresponding antibiotic-sensitive strain (MICs=78 μg/mL against each) and was significantly more potent against an ESBL K. pneumoniae strain (MIC=39 μg/mL) than against the corresponding antibiotic sensitive strain (MIC=78 μg/mL). All extracts were non-toxic in the Artemia nauplii lethality assay (ALA), indicating their safety for topical use. Conclusion: The potency of the E. major and M. alternifolia extracts against multi-antibiotic resistant bacteria and their lack of toxicity highlight these species as potential targets for antibiotic drug development. Further phytochemical and mechanistic studies of these species are warranted.
Keywords: Myrtaceae; Australian plants; Multi-drug resistant bacteria; Superbugs; β-lactamase; ESBL; MRSA.